L’enseignant·e d’EPS au prisme de la « question trans » en milieu scolaire - Bastien Pouy-Bidard (Éducation et Socialisation)
At a time when national education professionals are being asked to take "trans" students into account in the school environment, scientific papers on adults within the school is timidly emerging in the field of trans studies in education. As heuristic as these studies may be, it must be noted that this research very often considers academic actors as a monolithic entity, depriving the reader of a finer understanding of the difficulties they face. In PE, an eminently gendered discipline where norms are (de)constructed in action, are teachers true "out-of-peer" educators when it comes to welcoming a "trans" student? This article suggests investigating the place and role of teachers in this discipline in the light of the "trans issue" by placing their practices in perspective with those of their colleagues in the French national education system.